2017
DOI: 10.1523/jneurosci.1412-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Intercalated Cells (ITCs) in the Mouse Amygdala ofTshz1Mutants Correlates with Fear, Depression, and Social Interaction Phenotypes

Abstract: The intercalated cells (ITCs) of the amygdala have been shown to be critical regulatory components of amygdalar circuits, which control appropriate fear responses. Despite this, the molecular processes guiding ITC development remain poorly understood. Here we establish the zinc finger transcription factor Tshz1 as a marker of ITCs during their migration from the dorsal lateral ganglionic eminence through maturity. Using germline and conditional knock-out (cKO) mouse models, we show that is required for the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 109 publications
5
44
0
Order By: Relevance
“…The OFT was conducted on PP7, as previously described 49 . Motor activity was recorded for 1 h and data analyzed in 5-min intervals.…”
Section: Open Field Test (Oft)mentioning
confidence: 99%
See 1 more Smart Citation
“…The OFT was conducted on PP7, as previously described 49 . Motor activity was recorded for 1 h and data analyzed in 5-min intervals.…”
Section: Open Field Test (Oft)mentioning
confidence: 99%
“…The EZM was conducted on PP8, as previously described 49 . Amount of time spent in the open arms was recorded over a 5-min period.…”
Section: Elevated Zero Maze (Ezm)mentioning
confidence: 99%
“…DA is also released in the amygdala during affective states such as stress (Belujon and Grace, 2015; Yokoyama et al, 2005). Therefore, it is intriguing to speculate that dopaminergic modulation of distinct ITCs clusters may also play a role in other processes such as reward learning and addiction, as well as in the control of mood-related behavior such as anxiety- and depression-like behavior (Ferrazzo et al, 2019; Kuerbitz et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic lineage studies have shown that Gsx2-expressing LGE progenitors ultimately give rise to both neurons and glia (Kessaris et al, 2006;Fogarty et al, 2007;Qin et al, 2016). Accordingly, analysis of Gsx2 mutants revealed an essential role for Gsx2 in generating the above-mentioned LGE-derived neuronal subtypes (Toresson et al, 2000;Corbin et al, 2000;Yun et al, 2001;Waclaw et al, 2009Waclaw et al, , 2010Kuerbitz et al, 2018). Gsx2 regulates the generation of these neuronal subtypes through the upregulation of the proneural basic helix-loop-helix (bHLH) factor Ascl1 (Toresson et al, 2000;Corbin et al, 2000;Yun et al, 2001;Waclaw et al, 2009;Wang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%